Firm Size as a Moderating Variable of the Effect of Liquidity and Profitability on Firm Value - Noni Marliyana; Hadi Pramono; Sri Wahyuni; SEB Santoso (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine company size as a moderating variable in the relationship between liquidity and profitability and the value of LQ45 companies from financial reports listed on the Indonesia Stock Exchange for 2020-2022. The sampling method uses purposive sampling to produce 61 companies. The data analysis model uses Moderated Regression Analysis. The results of this research shows liquidity does not affect company value; profitability has a positive effect on company value; in company size is unable to moderate the relationship between liquidity and company value; in company size is unable to moderate the relationship between profitability and company value